RETRACTED: Genetic admixture history and forensic characteristics of Tibeto-Burman-speaking Qiang people explored via the newly developed Y-STR panel and genome-wide SNP data - He, Guanglin; Adnan, Atif; Al-Qahtani, Wedad Saeed; Safhi, Fatmah Ahmed; Yeh, Hui-Yuan; Hadi, Sibte; Wang, Chuan-Chao; Wang, Mengge; Liu, Chao; Yao, Jun (Frontiers in Ecology and Evolution, 2022)
Fine-scale patterns of population genetic structure and diversity of ethnolinguistically diverse populations are important for biogeographical ancestry inference, kinship testing and also for the development and validation of new kits focused on forensic personal identification. Analyses focused on forensic markers and genome-wide SNP data can provide new insights into the origin, admixture processes and forensic characteristics of targeted populations. Qiang people with a large sample size among Tibeto-Burman-speaking populations widely reside in the middle latitude of the Tibetan Plateau. However, their genetic structure and forensic features have remained uncharacterized due to the paucity of comprehensive genetic analyses. Here, we first developed and validated the AGCU-Y30 Y-STR panel, which contains slowly and moderately mutating Y-STRs, and then we conducted comprehensive population genetic analyses based on Y-STRs and genome-wide SNPs to explore the admixture history of Qiang people and their neighbours. The validated results of this panel showed that the new Y-STR kit was sensitive and robust enough for forensic applications. Haplotype diversity (HD) ranging from 0.9932 to 0.9996 and allelic frequencies ranging from 0.001946 to 0.8326 in 514 Qiang people demonstrated that all included markers were highly polymorphic in Tibeto-Burman people. Population genetic analyses based on Y-STRs (RST, FST, MDS, NJ, PCA and MJNs) revealed that the Qiang people harboured a paternally close relationship with lowland Tibetan-Yi corridor populations. Furthermore, we made a comprehensive population admixture analysis among Eurasian modern and ancient populations based on the shared alleles. We determined that the Qiang people were a genetically admixed population and showed the closest relationship with Tibetan and Neolithic Yellow River farmers. Admixture modelling showed that Qiang people shared the primary ancestry with Tibetan and was derived from North China, supporting the hypothesis of common origin between Tibetan and Qiang people.